STAD in Online-Supported Blended Learning for Developing Students’ Social Competence: A Classroom Action Research Study - Anwar Sewang; Muhammad Aswad (CV FOUNDAE, 2026)
By utilizing digital media support, this research will be examining the utilization of STAD cooperative learning model within blended learning framework. The research is centred on solving the issue of insufficient social interaction and cooperation in technology-assisted learning situations. In this research, Classroom Action Research was used for two cycles, in which the participants were 28 students from class VII-A of SMP Negeri 1 Sendana. Data gathering was done through classroom observation, teacher's reflective journal, structured interview, and documentation of face-to-face and online learning experiences. Interactive data analysis was carried out through three approaches: data condensation, data display, and drawing conclusions. Student social skills were measured using five criteria: self-confidence, accountability, motivation to learn, creative thinking, and digital communication. From the results of the study, it can be seen that the introduction of STAD strategy in the blended learning model led to peer interaction, individual accountability in working in groups, participation in discussion activities, and effective use of digital communication tools. All five elements showed significant progress on part of the learners, particularly after implementing changes into the teaching process in the second cycle. Still, some challenges appeared while implementing this strategy, including different levels of digital literacy, poor quality of Internet access, and various distractors during group work. To conclude, the study proved that collaborative learning through STAD is extremely efficient in building social competence